Verification of a Sense of Community Scale for Hospitals in Japan. (June 2022) - Goto, Ryohei; Haruta, Junji; Ozone, Sachiko
Introduction/Objectives: We aimed to verify whether a sense of community scale developed for hospital wards can be applied to hospitals. Methods: A cross-sectional study was conducted using a self-administered questionnaire between July and October 2018 in 3 hospitals in Japan. The subjects were staff members working in these hospitals who provide direct medical or administrative services to patients and their families. The questionnaire inquired about the participants' basic attributes and workplace satisfaction, and included the sense of community scale and the Japanese version of the Assessment of Interprofessional Team Collaboration Scale-II. We evaluated the scale's structural validity, internal consistency, and hypothesis testing for construct validity. Results: Of 826 eligible staff members, 539 were included in the analysis. Mean age was 40.4 years and 77.4% were female. Exploratory factor analysis showed that 24 of the 28 items in the sense of community scale could be categorized under 3 factors. Confirmatory factor analysis demonstrated a goodness of fit index of 0.794, adjusted goodness of fit index of 0.752, comparative fit index of 0.885 and root mean square error of approximation of 0.092. Cronbach's α for score in the sense of community scale was high (.96). Participants who reported high workplace satisfaction had significantly higher scores in the sense of community scale than those who indicated low workplace satisfaction ( P  < .001). Conclusions: We verified the reliability and validity of the Japanese version of the sense of community scale, which was originally developed for hospital wards, for the community in hospitals. With further verification, we hope the scale will be useful for evaluating the sense of community in hospitals.